Designing Vocabulary-Based Picture Flashcards to Support Seventh Grade Students’s Vocabulary Writing at Junior High School - Ziyan Putri Meliani; Isyarotullatifah; Ni Putu Artila Dewi; Kadek Lina Kurniawati; Aditya Ridho Fatmawan (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aimed to design and develop vocabulary-based picture flashcards as a learning medium for seventh-grade students at junior high school. The study employed the Research and Development (R&D) method using the ADDIE model, limited to the Analysis, Design, and Development stages, followed by expert validation and students’ responses. Data were collected through observation, interviews, questionnaires, and expert validation. The participants consisted of two material experts, two media experts, one English teacher, three students in the individual trial, sixteen students in the large-group trial, and thirty-three students in the field trial. The findings showed that the developed flashcards obtained a score of 87.67% from material experts, 96.67% from media experts, and 94.00% from the English teacher. Furthermore, students’ responses reached 87.33% in the individual trial, 78.75% in the large-group trial, and 83.15% in the field trial. These results indicate that the developed flashcards are highly appropriate and suitable for vocabulary writing activities among seventh-grade students.